1999
DOI: 10.1111/1468-0009.00138
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Processes of Care in Diverse Populations

Abstract: Persons of lower socioeconomic status and members of racial and ethnic minority groups experience poorer health and increased health risk factors. A framework of interpersonal processes of care specifies distinct components and incorporates the perspective of diverse racial and ethnic or socioeconomic groups. Its dimensions, each with several domains, are communication (general clarity, elicitation of and responsiveness to patient concerns, explanations, empowerment), decision making (responsiveness to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
177
0
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(194 citation statements)
references
References 85 publications
5
177
0
12
Order By: Relevance
“…15 Trust was assessed with two items adapted from the Trust in Physicians Scale. 16,17 Shared decision-making was assessed with two items modified from the Interpersonal Processes of Care Instrument, 18,19 one of which is similar to a CAHPS supplementary item (see Table 2 for specific item wording). 15,20 To simplify the survey and improve consistency across items, the time frame (last 12 months) and response choices ("never", "sometimes", "usually", and "always") from the CAHPS were employed for all items.…”
Section: Methodsmentioning
confidence: 99%
“…15 Trust was assessed with two items adapted from the Trust in Physicians Scale. 16,17 Shared decision-making was assessed with two items modified from the Interpersonal Processes of Care Instrument, 18,19 one of which is similar to a CAHPS supplementary item (see Table 2 for specific item wording). 15,20 To simplify the survey and improve consistency across items, the time frame (last 12 months) and response choices ("never", "sometimes", "usually", and "always") from the CAHPS were employed for all items.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on the information giving aspect of communication, the Interpersonal Processes of Care Framework (IPC) was incorporated to provide further conceptual and operational definitions to the communication process (Stewart, Nápoles-Springer, & Pérez-Stable, 1999). A review of the communication literature and clinical experience with diverse racial/ethnic and socioeconomic groups inform the operational definitions of concepts in the IPC Survey.…”
Section: Communication Process: Conveying and Receiving Messagesmentioning
confidence: 99%
“…A review of the communication literature and clinical experience with diverse racial/ethnic and socioeconomic groups inform the operational definitions of concepts in the IPC Survey. Specifically, the quality of communication describes the provider's clarity of messages and explanations of the condition and self-care (messages conveyed from provider to parent), as well as how well the provider elicits concerns and encourages decision-making (messages conveyed from parent to provider) (Stewart et al, 1999). This study used 15 IPC items to measure parents' perceptions of the quality of the communication process (Stewart et al, 1999).…”
Section: Communication Process: Conveying and Receiving Messagesmentioning
confidence: 99%
“…Those who reported that their diabetes control would be "better" or "much better" were considered to have perceived communication benefit. This is a novel question which was designed to avoid the ceiling effect commonly observed in assessments measuring patients' satisfaction with their patient-provider communication (46). Using the measure, we sought to explore whether patient's perceived need for better communication might influence their desire for and acceptability of different approaches to providing self-management support above and beyond socio-demographic and other diabetesspecific domains described above.…”
Section: Perceived Benefit Of Improved Communication-inmentioning
confidence: 99%
“…The gap between evidence and practice may be particularly important in safety net settings, such as public hospital systems, that care for a disproportionate share of ethnically diverse and socio-economically vulnerable patients (41,42), often with very limited resources. Racial/ ethnic minorities and those with limited English proficiency often experience especially poor communication in clinical settings (43)(44)(45)(46)(47)(48)(49)(50). These communication disparities are thought to contribute, in turn, to health disparities (51,52).…”
Section: Introductionmentioning
confidence: 99%